2022
DOI: 10.1177/08901171211070951
|View full text |Cite
|
Sign up to set email alerts
|

How Misinformation Research Can Mask Relationship Gaps that Undermine Public Health Response

Abstract: 14. Slotnik DE. Whistle-Blower unites democrats and republicans in calling for regulation of Facebook. New York Times. https:// www.nytimes.com/live/2021/10/05/technology/facebookwhistleblower-frances-haugen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A.J. Calac et al reported that healthcare professionals and all those working in the public health arena need to build and display trust in order to dispel the widespread dissemination and acceptance of false information in this technological age [35].…”
Section: Discussionmentioning
confidence: 99%
“…A.J. Calac et al reported that healthcare professionals and all those working in the public health arena need to build and display trust in order to dispel the widespread dissemination and acceptance of false information in this technological age [35].…”
Section: Discussionmentioning
confidence: 99%